Management of Desmoid Disease in Familial Adenomatous Polyposis - Sommovilla, Joshua; Shepard, Dale; Liska, David (Clinics in Colon and Rectal Surgery, 2023)
Desmoid disease, though technically a benign condition, is nevertheless a leading cause of morbidity and mortality in patients with familial adenomatous polyposis (FAP). Desmoid disease impacts approximately 30% of FAP patients, with several known risk factors. It runs the gamut in terms of severity—ranging from small, slow-growing asymptomatic lesions to large, focally destructive, life-threatening masses. Desmoids usually occur following surgery, and several patient risk factors have been established, including female sex, family history of desmoid disease, 3′ APC mutation, and extraintestinal manifestations of FAP. Desmoid disease-directed therapy is individualized and impacted by desmoid stage, severity, postsurgical anatomy, and consequences of disease. Medical therapy consists of options in multiple classes of drugs: nonsteroidal anti-inflammatory drugs, hormonal therapy, tyrosine kinase inhibitors, and cytotoxic agents. Surgical excision is sometimes an option, but can be limited by common location of disease at the root of the small bowel mesentery. Palliative surgical treatments are often considered in management of desmoid disease. Intestinal transplantation for severe desmoid disease is an emerging and promising option, though long-term data on efficacy and survival is limited.
Keywords: familial polyposis; desmoid; APC; fibromatosis